Studies on the causation of adverse reactions in microfilaraemic host following diethylcarbamazine therapy (Dipetalonema viteae in Mastomys natalensis) - Singh, D.P; Rathore, S; Misra, S; Chatterjee, R.K; Ghatak, S; Sen, A.B (Tropical medicine and parasitology, 1985)
The mechanism of the adverse reaction in microfilaraemic subjects following diethylcarbamazine (DEC) therapy has remained an enigma. To study the mechanisms involved Mastomys natalensis infected with Dipetalonema viteae have been used. Animals showing up to 50 mf/5 cmm of blood did not show any perceptible reactions when treated with the minimum effective dose of 350 mg/kg of DEC citrate, while those having more than 80 mf/5 cmm died, suggesting an intensity dependent severity of reactions. Infective larvae contained maximum amounts of biogenic amines followed by mf and adults in that order. 16 mg of histamine or 24 mg of 5-hydroxytryptamine caused death when injected into healthy animals, whereas sonicated mf (5 million) and adult somatic products (4 mg protein) did not, signifying that the biogenic amine contents of the parasites were less than the critical level to cause death. Adult somatic products did not produce any visible reactions when injected into animals with microfilariaemia, but sonicated mf (5 million) caused death. It is concluded that the adverse reactions seen after DEC treatment are due to the release of biogenic amines in an anaphylactic type of reaction subsequent to massive release of parasite antigen in a sensitised host, which is directly proportional to the intensity of microfilaraemia and that the adverse reactions are not due to liberation of endogenous biogenic amines from dead mf.